The relationship between faculty interactions, sense of belonging, and academic stress: a comparative study of the post-COVID-19 college life of Korean and international graduate students in South Korea - Kim, Dongil; Woo, Yeyoung; Song, Jusuk; Son, Subin (Frontiers in Psychiatry, 2023)
Rapid changes in post-COVID-19 higher education have increased students’ academic stress. This study focused on graduate students’ academic stress in South Korea and compared the results for Korean graduate students and those for international graduate students based on online survey results. The study verified the relationships between faculty interactions, a sense of belonging, and academic stress among Korean and international graduate students using a mediating effects analysis and a multigroup path analysis. The results were as follows. First, Korean students experienced greater academic stress, faculty interactions, and a sense of belonging, but no statistically significant difference was observed. Second, a sense of belonging had a mediating effect on the relationship between faculty interactions and academic stress. Unlike in previous studies, all paths were found to be statistically significant. Faculty interactions had a negative effect on academic stress and a positive effect on a sense of belonging. A sense of belonging had a negative effect on academic stress. Third, the comparison of Korean and international graduate students showed that international students had a greater effect of faculty interactions on academic stress. Through these results, we explored the post-COVID-19 academic lives of Korean and international graduate students in South Korea and built grounds for effective interventions for alleviating academic stress.